On-Surface Modification of Copper Cathodes by Copper(I)-Catalyzed Azide Alkyne Cycloaddition and CO2 Reduction in Organic Environments - Igarashi, Ryota; Takeuchi, Ryuji; Kubo, Kazuyuki; Mizuta, Tsutomu; Kume, Shoko (Frontiers in Chemistry, 2019)
Organic structures were introduced onto copper cathodes to induce changes to the electrocatalytic CO2 reduction activity. Poorly soluble organic polymers were distributed onto the copper surface as a thin layer, by polymerizing monomeric precursors via a copper(I)-catalyzed azide alkyne cycloaddition (CuAAC) activated by anodization of the copper substrate. The resulting structure possesses copper surface atoms that are accessible to participate in the CO2 reduction reaction—comparable to close-contact organic structures—and stabilize the adsorption of organic layers through the CO2 reduction process. The CO2 reduction performance of the on-surface modified copper cathode exhibited improved CO2 reduction over H2 evolution, compared with traditional cast modification systems. Preventing organic moieties from forming densely-packed assemblies on the metal surface appears important to promote the CO2 reduction process on the copper atoms. The suppression of H2 evolution, a high methane/ethylene ratio and the influence of stirring demonstrates that the improved CO2 reduction activity is not only as a result of the copper atom reorganization accompanied by repeating anodization for modification. Additionally, the organic layer apparently plays an important role in proton transfer and CO2 accumulation onto the copper surface.